Respuesta :
to expand this logarithm, we have to apply the rules. These rules are;
Log(A/B) = logA - LogB and Alogx=log(x∧A)
Log (x³/z∧5) = log (x³) - log z∧5
=3log x - 5log z
Log(A/B) = logA - LogB and Alogx=log(x∧A)
Log (x³/z∧5) = log (x³) - log z∧5
=3log x - 5log z
Using the following properties we can expand the given expression:
1) Quotient Rule of Logs:
Log(A/B) = Log A - Log B
2) Power Rule of Logs:
[tex]Log(a)^{b}=b*Log(a) [/tex]
[tex]log( \frac{ x^{3} }{ z^{5} } ) \\ \\ =log( x^{3})-log( z^{5}) \\ \\ =3logx-5logz[/tex]
1) Quotient Rule of Logs:
Log(A/B) = Log A - Log B
2) Power Rule of Logs:
[tex]Log(a)^{b}=b*Log(a) [/tex]
[tex]log( \frac{ x^{3} }{ z^{5} } ) \\ \\ =log( x^{3})-log( z^{5}) \\ \\ =3logx-5logz[/tex]